The complete chloroplast genome of Pholidota yunnanensis Rolfe (Orchidaceae: Coelogyninae) - Wu, Qiu-Ping (Mitochondrial DNA B Resour, 2020)
In this study, the complete chloroplast genome of Pholidota yunnanensis is presented, which represents first complete plastid genome of the genus Pholidota in the subtribe Coelogyninae. The chloroplast genome size is 159,729 bp, including a GC content of 37.3% and 135 genes (89 protein-coding genes, 38 tRNA genes, 8 rRNA genes). The genome structure is typical quadripartite, consisting of a pair of inverted repeat regions (26,638 bp) separated by a large single-copy region (LSC, 87,610 bp) and a small single-copy region (SSC, 18,843 bp). Phylogenetic analysis among 15 species based on cp genomes recovered a well-supported phylogenetic tree and indicated a close relationship between Pholidota yunnanensis and Pleione bulbocodioides.